2019
DOI: 10.1186/s12879-019-3852-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and correlates of virological failure among adult HIV patients receiving PI based second line ART regimens in north western Tanzania; a case control study

Abstract: Background With a growing access to free ART, switching of ART to second line regimen has also become common following failure of first line ART regimens. Patients failing on first line ART regimens have been shown to stand a high risk of failing on subsequent second line ART regimens. The magnitude of those who are failing virologicaly on second line ART is not documented in our setting. This study was designed to assess the magnitude and correlates of second line ART treatment failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In addition, the study found that a baseline CD4 count of greater than 100cells/mm3 is a protective factor for first-line ART treatment failure. For this finding similar existing evidences upkeep this finding [ 17 , 20 22 ]. This suggests the higher CD4 count, the lower viral load which protects against treatment failure.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the study found that a baseline CD4 count of greater than 100cells/mm3 is a protective factor for first-line ART treatment failure. For this finding similar existing evidences upkeep this finding [ 17 , 20 22 ]. This suggests the higher CD4 count, the lower viral load which protects against treatment failure.…”
Section: Discussionsupporting
confidence: 81%
“…The association between adherence and treatment failure was based on six cross-sectional studies [ 14 , 35 , 37 , 40 , 42 , 47 ]. The results as presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is line with a study conducted in south Africa and Northwestern Tanzania which shows poor adherence was a strong predictor of second-line ART failure. 12,19 In Rwanda and Kenya, patients who were on second line ART with good adherence to ART were also significantly associated with viral suppression. 20,21 It is evident that individuals missing more than three doses from BID dose or more than one dose from daily dose of ART per month are associated with an increased risk of virological failure, leading to reduced immunity.…”
Section: Discussionmentioning
confidence: 99%
“…11 A higher rate of virological failure of 17.7% was reported in India among patients who were on second line ART beyond 1 year and a much higher rate of virological failure of 37% was also recently reported from Myanmar Asia among patients who were on second line ART. 12 In a resource limited setting the rates of second-line failure have been demonstrated to be as high as 38% by 36 months. 13 The three 90 treatment target sets the goal by 2020: 90% of people living with HIV knowing their HIV status, 90% of people who know their HIV-positive status accessing treatment, and 90% of people on treatment having suppressed viral loads.…”
Section: Introductionmentioning
confidence: 99%